PERAN PEMERINTAH DALAM PEREKONOMIAN DALAM PERSPEKTIF ISLAM - Lc., M.EI,, Misbahul Munir, (Fakultas Ekonomi, UIN Maliki Malang, 2006)
As universal religion, Islam do not only arranging human life individually. But further than these phenomena, Islam becomes as â€œrahmatan lil â€˜alaminâ€, Islam arranges how to systemically the life, than the life can walk consecutively, prosperous and fair. In this case, the government, as the institution, who has getting mandate of Allah of swt, and the people at the same time have the strategic role and the responsibilities to realize the universal values.From this discussions, can be known that the governmental interventionâ€™s applied for guarantee economics system, than this economics system can be walking on the Moslemâ€™s law, and on the code and also on the plan of development of state. The Government in Islam has the right to intervencing the economics of the state, in order to executing him responsibilities to upholding the justice of economics and prosperity of the people.The Governmental interventionâ€™s in Islam at the same timeâ€™s can be link the economic system of capitalist which tend to infinite free and the socialist system which tend to hijack the freedom of individual economics. As the concrete step/action, the government agreed to hold the conduct resource to cover the commonâ€™s interest, to managing and distributing it fairly, the intervence takes care of marketâ€™s stability and also to control and to observe the matching system with the justice principles and the prosperity of the society.